Alzheimer's disease: Related targets, synthesis of available drugs, bioac-tive compounds under development and promising results obtained from multi-target approaches - Pirolla, Natália F. F. [UNESP]; Batista, Victor S. [UNESP]; Viegas, Flávia Pereira Dias; Gontijo, Vanessa Silva; McCarthy, Caitlin R. [UNESP]; Viegas, Claudio; Nascimento-Júnior, Nailton M. [UNESP] (Bentham Science Publishers, 2021)
We describe herein the therapeutic targets involved in Alzheimer’s disease as well as the available drugs and their synthetic routes. Bioactive compounds under development are also exploited to illustrate some recent research advances on the medicinal chemistry of Alzheimer’s disease, including structure-activity relationships for some targets. The importance of multi-target approaches, including some examples from our research projects, guides new perspectives in search of more effective drug candidates. This review comprises the period between 2001 and early 2020.
Keywords: Acetylcholinesterase; Alzheimer’s disease; Multi-target-directed ligands; Nicotinic acetylcholine receptors; Structure-activity relationship; Synthetic routes